NURSE'S COMMUNICATIVE ACT IN THE CARE TO THE CRITICALLY ILL PATIENT - Kelly Karine Sales Zem; Fabíola Schirr Cardoso; Juliana Helena Montezeli (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976927419 Objective: reflect on the nurse's communicative act in the care to the critical patient. Method: this is a theoretical reflection. Results: two reflective categories were constructed, in the first there was a brief explanation of Jürgen Habermas' Theory of Communicative Act, constituting a backdrop for the second reflection stage, which presented considerations on the interfaces of that theory with the nurse's action when providing critically ill individuals with care. Conclusion: through literature analysis, one concludes that the theoretical framework concerned may contribute to the humanization of nursing care to the patient in a critical condition, since, by submitting his attitudes to a communicative act, the nurse will be in search of a greater interaction with the patient, the family, his team, and the other health professionals.